Effect of municipal organic waste compost for sustainable maize production in arid land agriculture - Hossain, Shahadat; Samir G. M. Al-Solaimani,; Alghabari, Fahad; Shahzad, Khurram; I. Rashid, Muhammad (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
Effective use of municipal organic waste (MOW) derived composts for soil nutrient management is crucial for sustainable crop production and environmental protection. Maize cultivation using MOW compost is economical and environmentally beneficial around the world. Adding MOW compost to the soil improves maize yield. A field study was conducted in 2022 and 2023 to determine the effects of two composts made from MOW mixed with Vermiculite, Cow dung, and NPK fertilizer at three levels (5, 10, and 15 ton/ha) on maize yield and yield components. Three replications split plot statistical design. Main plots had compost levels, while subplots had four MOW waste composts: MOW, Vermiculite + MOW, Cow manure +MOW, and 125 kg/ha NPK fertilizer with MOW. Each 6 m2 plot had a 50 cm line-to-line and 30 cm plant-to-plant distance. MOW compost with NPK fertilizer had the greatest impact on yield and yield-related characteristics, followed by Vermiculite and Cow manure compost at 15 ton/ha. Finally, MOW mixes with NPK at 15 ton/ha performed best for all maize characteristics. This qualitative and quantitative analysis will not only shed fresh light on converting MOW to compost in the context of arid land agriculture but will also pave the way for a substantial and worthwhile expansion of maize production.